Lifestyle Modification for the Prevention and Management of Elevated Blood Pressure and Hypertension in Adults: A Systematic Review - Gbenga Abraham Arajulu (Journal of Public Health, Policy, and Society, 2026)
Background: Lifestyle modification is recommended across contemporary hypertension guidelines, yet the recent comparative intervention literature spans heterogeneous diets, exercise prescriptions, behavioural programmes, digital tools, and implementation settings. Objective: To systematically identify and narratively synthesize primary comparative studies of lifestyle modification for prevention or management of elevated blood pressure and hypertension in adults. Methods: PubMed and Cochrane CENTRAL were searched on 6 August 2026 for English-language reports published from 1 January 2016. Comparative randomized, cluster-randomized, crossover, and non-randomized interventions lasting at least four weeks were eligible. Grey literature, protocols, secondary evidence syntheses, pregnancy, pediatric populations, acute exposures, and interventions without an isolatable lifestyle component or blood-pressure effect were excluded. Screening, extraction, and provisional risk-of-bias appraisal were conducted in a structured single-reviewer workflow with rule-based assistance and manual adjudication. Owing to clinical and methodological heterogeneity, results were synthesized without meta-analysis. Results: The searches identified 9,151 records; 1,493 duplicates were removed and 7,658 unique records were screened. Of 589 reports sought, 244 full texts were obtained and assessed; 151 reports representing 144 unique studies were included. The evidence base comprised 109 individually randomized trials, 15 cluster-randomized trials, 10 randomized crossover trials, and 10 non-randomized comparative interventions. Exercise or physical activity was most common (40 studies), followed by multicomponent lifestyle programmes (21), digital or remote self-management (20), sodium reduction or salt substitution (19), mind-body or stress-reduction interventions (14), dietary pattern or food-based interventions (13), and education/coaching/self-management (10). Most reports described favourable blood-pressure changes, but effect magnitude and consistency varied. Structured exercise, sodium reduction, culturally adapted dietary patterns, and intensive multicomponent programmes produced the most recurrent benefits; digital and educational interventions were more dependent on engagement, intensity, and co-interventions. Provisional appraisal identified one study with low risk, 121 with some concerns, and 22 at high risk of bias. Conclusions: Recent comparative evidence supports lifestyle modification as a clinically meaningful component of both hypertension prevention and management, especially when interventions are sustained, behaviourally supported, culturally adaptable, and linked to reliable blood-pressure monitoring. Confidence in precise comparative effects is limited by heterogeneity, incomplete reporting, inaccessible full texts, and review-process constraints. The evidence supports implementation alongside - not as a reason to delay - pharmacological therapy when guideline thresholds require medication. Registration: No protocol was registered. The absence of prospective registration is a limitation.